2012
DOI: 10.1515/polyeng-2011-0118
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated polyester-clay slurry nanocomposites

Abstract: In this work, nanocomposites were produced with an unsaturated polyester resin and sodium montmorillonite (MMT) slurry. Upon increasing the clay content [from 1 to 5 parts per hundred resin (phr)] increments of 57 % and up to 120 % were found in the fl exural modulus, with respect to that of the resin alone. Using clay slurry, the cross-linking reaction was affected by the clay, in such a way that the gelation temperature and the thermal stability increased. Using transmission and scanning electron microscopy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…However, the moisture content may also increase clay viscosity and inhibit clay dispersion [18]. In addition, the moisture content may function as lubricant that reduces shear and interfacial bonding in composites [19,20]. These caused the low modulus for UDC samples.…”
Section: Resultsmentioning
confidence: 99%
“…However, the moisture content may also increase clay viscosity and inhibit clay dispersion [18]. In addition, the moisture content may function as lubricant that reduces shear and interfacial bonding in composites [19,20]. These caused the low modulus for UDC samples.…”
Section: Resultsmentioning
confidence: 99%
“…It is quite evident from Figure 7 that among all nanocomposite samples, UPN5 and UPC1 exhibit the highest thermal stability and the lowest rate of mass loss when compared with UPL5 and pristine UP. Rivera-Gonzaga et al 26 reported that upon UP intercalation, increased interaction between UP and the clay surface may be induced through carboxylic groups in the chain ends as well as van der Waals interactions among the UP ester group and the clay surface. These interactions lead to decrease the mass loss rate and consequently to better thermal stability.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Jawahar et al demonstrated that nanocomposites with different clay contents exhibit an improvement of 85% in wear resistance and a decrease of 35% in the friction coefficient . On the other hand, the addition of montmorillonite particles into polyester resin reduced the coefficients of thermal expansion (CTE), bending and tensile testes revealed that higher percentages of montmorillonite induced higher Young's modulus . Numerous researchers have been reported that the addition of a nanoclay in amounts of 0.5–1% increases the viscosity of UP resin; whereas, the gel time and the degree of shrinking are decreased.…”
Section: Introductionmentioning
confidence: 99%